PENGUJIAN KARTU FTA SEBAGAI ALAT SAMPLING DNA JAMUR PATOGEN DARIBERBAGI BAGIAN TANAMAN YANG TERINFEKSI - Purnamila Sulistyawati (Jurnal Pemuliaan Tanaman Hutan, 2011)
FTA  card offers a simple and fast method for retrieval of DNA samples at room temperature and storage of DNA in the short and long term. This will fasiliate the detection and identification of plant pathogens rapidly; increasing the number of samples can be collected, stored and transported in the field, especially from remote locations. The purpose of this study is to investigate  the suitability of FTA cards as a new method for sampling DNA from multiple infected of  plant tissues such as leaves, bark and roots. The results of this study shows that the FTA card suitable for use as one method of smpling because its quick and accurate. Series of PCR using ITSIF/ITS4 and ITS3/ITS4 primer pairs were done to detect the fungal DNA from the FTA card Nested PCR has been done using species – specific primers to identify the fungus without cloning. Optimization of methods to maximize the use of FTA cards as a method of sampling and DNA extraction which is simple, fast, accurate and safe for the environment is still needed.